Understanding the Development, Standardization, and Validation Process of Alternative In Vitro Test Methods for Regulatory Approval from a Researcher Perspective. Issue 15 (22nd January 2021) - Bas, Aurora; Burns, Nicole; Gulotta, Andrew; Junker, James; Drasler, Barbara; Lehner, Roman; Aicher, Lothar; Constant, Samuel; Petri‐Fink, Alke; Rothen‐Rutishauser, Barbara
Abstract: Due to economic, practical, ethical, and scientific reasons, researchers, among others, are pushing for alternative in vitro test methods to replace or reduce existing animal experiments. In order for these tests to be more broadly used by the industrial sector and regulatory bodies, orchestrated efforts are required to show the robustness and reliability of in vitro methods, which can accelerate the use for early screening testing. Another way of increasing the use of alternatives is to coordinate validation studies, that is, multi‐laboratory trials, and to gain regulatory approval and instatement as test guidelines or standard method. However, awareness of the exact standardization, validation, and approval process has been a major obstacle for many researchers. Herein, the process has been broken down into three main phases: i) test method development; ii) intra‐ and inter‐laboratory validation; and iii) regulatory acceptance. This general process applies to all alternative methods seeking validation and approval, although the intricacies of different toxicological endpoints and/or chemical sectors may lead to additional work, particularly in the validation stage. The authors' aim is to provide insight in the development process of alternative methods with a focus on in vitro cell culture methods over validation to regulatory acceptance. Abstract : There is a need for hazard testing in regulatory toxicology and biomedical research in the context of the 3Rs concept. From a researcher's perspective, insight is provided into the development process of alternative methods with a focus on in vitro cell culture methods through validation to regulatory acceptance.